Body dissatisfaction in adolescence. Changes in a decade - Bully, Paola; Elosua, Paula; López Jáuregui, Alicia (Anales de Psicología / Annals of Psychology, 2012)
This study examines the changes in adolescents’ body image and body mass index over the last 11 years. Data came from two different subsamples collected in the years 1997 (n = 3468) and 2008 (n = 846). The body image was assessed by the Body Dissatisfaction scale belonging to Eating Disorder Inventory (Garner, 1998, 2004). The results showed that the Body Mass Index is an important covariable in the study of the body dissatisfaction. The body dissatisfaction mean values decreased in the fe- male sample, although the observed reduction was not statistically significant. The male’s values didn’t change over the last 11 years.